Dental Subphenotypes in Infants With Orofacial Clefts—A Longitudinal Population-Based Retrospective Radiographic Study of the Primary and Secondary Dentitions. (November 2021) - Yow, Mimi; Hermann, Nuno V.; Wei, Yuan; Karsten, Agneta; Kreiborg, Sven
Objectives: To determine the developmental patterns of primary and secondary dentitions in infants with orofacial clefts. Design: Retrospective, longitudinal, population-based cohort study. Materials: Longitudinal records and radiographs of 192 nonsyndromic Northern European infants with isolated unilateral cleft lip (UCL, n = 111) and isolated cleft palate (CP, n = 81). Methods: Radiographic assessments of primary and secondary dentition anomalies and dental maturation, by gender and cleft severity for comparisons between the groups and with historical controls. Results: In infants with UCL, the frequencies of dental anomalies were high in both primary (38.7%) and secondary (18.0%) dentitions. Primary and secondary dentition anomalies were not observed in infants with CP and different in the UCL group ( P = .003). Risk differences involved primary supernumerary teeth ( P = .0001) and talon cusp formation ( P = .0001), and secondary tooth agenesis ( P = .001) of the maxillary lateral incisor on the side of the cleft lip. Delayed primary and secondary dental maturation occurred in the UCL and CP groups, greater in infants with UCL ( P < .0001). Primary and secondary dental maturation featured sexual dimorphism with greater delay in males (UCL, P < .0001; CP, .0001 > P = .001). The effect of cleft severity on dental maturation was significant in infants with UCL ( P = .0361) and CP ( P = .0175) in the primary but not in the secondary dentition. Conclusions: There were different dental anomalies in the primary and secondary dentitions in operated infants with UCL and no dental anomalies in unoperated infants with CP. Dental maturation was delayed in infants with UCL and CP with greater delay in males compared to females.